2008
DOI: 10.1126/science.1156609
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inhibition of the Alzheimer's Disease β-Secretase by Membrane Targeting

Abstract: beta-Secretase plays a critical role in beta-amyloid formation and thus provides a therapeutic target for Alzheimer's disease. Inhibitor design has usually focused on active-site binding, neglecting the subcellular localization of active enzyme. We have addressed this issue by synthesizing a membrane-anchored version of a beta-secretase transition-state inhibitor by linking it to a sterol moiety. Thus, we targeted the inhibitor to active beta-secretase found in endosomes and also reduced the dimensionality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
199
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(211 citation statements)
references
References 26 publications
10
199
1
1
Order By: Relevance
“…It is further conceivable that reduction in Reelinsignaling promotes APP endocytosis because of reduced binding of the central Reelin domain to the N terminus of APP (Hoe et al, 2009). This scenario fits with previous data showing preferential APP ␤-secretase cleavage in endocytic vesicles (Rajendran et al, 2006(Rajendran et al, , 2008, in line with the reported endosomal localization and pH optimum of ␤-secretase activity (Vassar et al, 1999).…”
Section: Discussionsupporting
confidence: 79%
“…It is further conceivable that reduction in Reelinsignaling promotes APP endocytosis because of reduced binding of the central Reelin domain to the N terminus of APP (Hoe et al, 2009). This scenario fits with previous data showing preferential APP ␤-secretase cleavage in endocytic vesicles (Rajendran et al, 2006(Rajendran et al, , 2008, in line with the reported endosomal localization and pH optimum of ␤-secretase activity (Vassar et al, 1999).…”
Section: Discussionsupporting
confidence: 79%
“…The same quasiirreversible binding is achieved with a single cholesteryl moiety (47). The use of cholesterol for membrane targeting of a peptide has just been described to increase the potency of a transitionstate ␤-secretase inhibitor (48).…”
mentioning
confidence: 77%
“…Notably, in the only other reported example of cholesterol tethering to a peptide, the same absolute need for C-terminal versus N-terminal linkage of cholesterol was observed, and palmitoyl derivatization was inferior to cholesterol in promoting biological activity (48).…”
mentioning
confidence: 99%
“…To ensure their accumulation within endosomes, a membrane-anchored BACE1 transition-state inhibitor was linked to a sterol moiety. Because of its selective accumulation within endosomes, the membrane-bound inhibitor reduced BACE1 activity much more efficiently than a nonmembrane anchored version (Rajendran et al 2008). However, BACE1 activity is not exclusively restricted to endosomes.…”
Section: Trafficking and Proteolytic Processing Of Appmentioning
confidence: 99%